Microstructural analysis of laser coated ceramic components TiB sub 2 and TiC on aluminium alloy EN AW-6082-T651 - Ravnikar, Dunja (Strojniški vestnik, 2013)
This paper deals with the deposition of ceramic powder coating TiB2-TiC mix with aluminium powder on the 6082-T651 aluminium alloy by means of laser coating. The resulting coating was studied by means of a microstructural and microchemical analysis. Microhardness was measured in the coating and in the substrate area under the coating. A thermodynamic analysis of the system showed the potential existence of aluminium carbide Al4C3 in the coating, whereas the EDS analysis indicated a possible occurrence of aluminium oxycarbides in the coating, containing TiB2, TiC and Al. An additional thermal analysis explained the existence of two separate exothermic peaks, on the basis of which it could be inferred that the precipitation of phase Mg2Si, which is a typical precipitate in aluminium alloy 6082, occurred. Microhardness measurements confirmed the differences in the hardness of the coating, resulting from different energy input during the coating process. Due to the thermal effect of the coating process and the rapid cooling of the coating and the coating-substrate interface, microstructural changes occurred on the substrate surface under the coating. The modified microstructure under the coating resulted in reduced hardness, which could be attributed to the use of the alloys in the precipitation-hardened state. Thermal effects of the coating process and rapid cooling contributed to the occurrence of forced dissolution with reduced microhardness.
Keywords: aluminijeva zlitina; aluminium alloy; ceramic components; keramične sestavine; laser coating; lasersko oplastenje; microhardness; microstructure; mikrostrukturna analiza; mikrotrdota; termična analiza